The satisfaction of patients with chronic dermatoses according to the medical care they received - E. E. Ziltsova; L. R. Chakhoyan; O. E. Konovalov; M. A. Khodorovich (Исследования и практика в медицине, 2019)
The article deals with the opinion of patients about different activities of medical organizations. It was established that opinion of patients about the activities of medical organizations depends on many factors, among which the most important were the place of residence, social status, level of education, material security and others.Purpose of the study. To study the satisfaction of patients with chronic dermatoses with the medical care they receive in a metropolis.Materials and methods. The satisfaction of patients with chronic dermatoses with the quality of the services provided in dermatovenerological clinics was studied on the basis of a questionnaire survey of 412 patients living in Moscow. Results. It was established that 74.0% of patients were satisfied with the quality of dermatological care, 19.6% were more likely satisfied than not, 5.8% were more unsatisfied than yes, 0.6% were not satisfied. The attentive and friendly attitude of medical personnel to patients in polyclinic and inpatient departments of specialized medical organizations noted in 91.7% of respondents, inattentive — in 0.6% and found it difficult to answer — 7.7%. The majority of respondents (97.8%) rated the schedule of doctors as convenient and waiting time for a dermatovenerologist's appointment in the clinic is not long (96.8%).The minimum proportion of patients (1.3%) indicated a refusal to conduct the necessary in their opinion examinations and treatment.Conclusion. The majority of patients were satisfied with the specialized care received and practically had no difficulties visiting specialized medical organizations in view of their sufficient number in different areas of the city.